Microtubule Cytoskeleton Remodeling by Acentriolar Microtubule-organizing Centers at the Entry and Exit from Mitosis in Drosophila Somatic Cells - Moutinho-Pereira, S (2009)
Cytoskeleton microtubules undergo a reversible metamorphosis as cells enter and exit mitosis to build a transient mitotic spindle required for chromosome segregation. Centrosomes play a dominant but dispensable role in microtubule (MT) organization throughout the animal cell cycle, supporting the existence of concurrent mechanisms that remain unclear. Here we investigated MT organization at the entry and exit from mitosis, after perturbation of centriole function in Drosophila S2 cells. We found that several MTs originate from acentriolar microtubule-organizing centers (aMTOCs) that contain -tubulin and require Centrosomin (Cnn) for normal architecture and function. During spindle assembly, aMTOCs associated with peripheral MTs are recruited to acentriolar spindle poles by an Ncd/dynein-dependent clustering mechanism to form rudimentary aster-like structures. At anaphase onset, down-regulation of CDK1 triggers massive formation of cytoplasmic MTs de novo, many of which nucleated directly from aMTOCs. CDK1 down-regulation at anaphase coordinates the activity of Msps/XMAP215 and the kinesin-13 KLP10A to favor net MT growth and stability from aMTOCs. Finally, we show that microtubule nucleation from aMTOCs also occurs in cells containing centrosomes. Our data reveal a new form of cell cycle–regulated MTOCs that contribute for MT cytoskeleton remodeling during mitotic spindle assembly/disassembly in animal somatic cells, independently of centrioles.